Pesticide Injection and Drenching - Frederick Fishel; Adam Dale; Ryan W. Klein (EDIS)
Drenching and injection are two pesticide application methods that are particularly effective in controlling some of the most troublesome insect pests of ornamental landscape trees. This 4-page document describes the equipment and procedures you will need to carry out either of these methods. Written by Frederick M. Fishel and published by the UF/IFAS Agronomy Department, January 2018. http://edis.ifas.ufl.edu/pi274